Achieving Higher Performance: Enhancing Spending Efficiency in Health and Education in Mexico - Schwellnus, Cyrille (OECD Economics Department Working Papers, 2009)
Despite progress over the past two decades Mexico?s health and education indicators remain well below the average of the OECD and some of its Latin American emerging market peers. Health insurance coverage is incomplete, especially for low-income families, and access to health services is highly uneven. There are several separate vertically integrated insurance networks, which increases administrative costs and results in an inefficient use of facilities. In education, lower secondary schools enroll only two thirds of the relevant age group and the quality of education is low, as indicated by poor PISA scores. This reflects poor teaching quality, a consequence of non-transparent teacher selection processes until recently, and limited school autonomy in budgeting, instruction and personnel decisions. Accountability to the government and parents is also low as there is no national exit exam after secondary education and the existing evaluation schemes are fragmented. Recent health and education reforms have started to address these issues, but more needs to be done to increase the efficiency of spending by increasing the coverage of health insurance, reducing the fragmentation of the health system, increasing enrolment in lower secondary education, and improving the quality of teaching